1997
DOI: 10.1002/(sici)1099-0992(199705)27:3<337::aid-ejsp825>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Ingroup bias, self-enhancement and group identification

Abstract: These two studies integrate self-enhancement and ingroup bias and analyse the phenomena from the social identity theory and self-categorization theory. In Study 1, the subjects (N=181) evaluated supporters of two presidential candidates on a rating scale. In Study 2, the subjects (N=302) evaluated either Finnish women's and men's positive characteristics (success condition) or negative characteristics (failure condition) which might play a role in achieving equality between the sexes in Finland. Self-evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…In addition, what does the social psychology literature contribute in terms of acting White as it relates to in-group and out-group affiliations (see Abele & Petzold, 1996;Franco & Maass, 1996;Lindeman, 1997;Mackie & Ahn, 1998;Moy & Ng, 1996;Terry & Callan, 1998), given the general tendency to make stereotyped assumptions about out-groups (Harasty, 1997;Koomen & Dijker, 1997), as well as to view out-groups in a way that is more negative than one's own identified group (Harasty, 1997)? If the process is this complex for Whites as the in-group available as a behavioral model, the data presented suggest that the inference-making process, as experi-28 SPENCER, NOLL, STOLTZFUS, HARPALANI enced by African American adolescents, is even more complex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, what does the social psychology literature contribute in terms of acting White as it relates to in-group and out-group affiliations (see Abele & Petzold, 1996;Franco & Maass, 1996;Lindeman, 1997;Mackie & Ahn, 1998;Moy & Ng, 1996;Terry & Callan, 1998), given the general tendency to make stereotyped assumptions about out-groups (Harasty, 1997;Koomen & Dijker, 1997), as well as to view out-groups in a way that is more negative than one's own identified group (Harasty, 1997)? If the process is this complex for Whites as the in-group available as a behavioral model, the data presented suggest that the inference-making process, as experi-28 SPENCER, NOLL, STOLTZFUS, HARPALANI enced by African American adolescents, is even more complex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some individuals might show an opposite effect that neutralizes the positive association. Perceived age discrimination can increase in-group identification especially among older adults (Garstka et al 2004) which is in turn associated with a strengthened selfenhancement and more positive attitudes towards the ingroup (Kaiser et al 2009;Lindeman 1997), but also has been shown to have negative long-term effects (Pavalko et al 2003). These diverging consequences might tend to cancel out each other.…”
Section: Domain Specificity Of the Relation Of Views On Ageing And Pementioning
confidence: 99%
“…We reasoned that if the motives underlying the categorization bias reflect individuals' concern with the integrity of the in-group, then it is precisely the impact of in-group identification that needs assessment. Furthermore, identification with the in-group has proven to influence a number of phenomena, such as the in-group bias Jetten, Spears, & Manstead, 1996;Lindeman, 1997), the black sheep effect (Branscombe, Wann, Noel, & Coleman, 1993;Castano, Paladino, Coull, & Yzerbyt, 2001;Coull, Yzerbyt, Castano, Paladino, & Leemans, 2001), and the perception of in-group homogeneity Doosje, Ellemers, & Spears, 1995;Kelly, 1989), all of which could be considered strategies to enhance and protect the image of the in-group (Castano, 1999, in press;Doosje & Ellemers, 1997;Leyens et al, 1994;Yzerbyt, Castano, Leyens, & Paladino, 2000).…”
Section: Social Identity and Categorizationmentioning
confidence: 99%